Impacts of a nutrition education intervention in individuals with cardiometabolic risk: Protocol of a randomized controlled trial - Chiang, Wan Ling; Mohd Yusof, Barakatun Nisak; Azlan, Azrina; Ismail, Irmi Zarina; Abu Zaid, Zalina (Elsivier, 2022)
Background: Unhealthy dietary pattern including high dietary sugar intake is responsible for the cardiometabolic-related deaths. Nonetheless, adherence to the recommendation is low, and appropriate nutrition education to reduce sugar consumption is scarce. Objective: This proposed project aims to evaluate the effectiveness of a nutrition education module in modifying sugar consumption and other cardiometabolic risk (CMR)-related outcomes in individuals with CMR. Methods: This is an open-label, 3-group parallel-randomized controlled trial that will be conducted in Universiti Putra Malaysia, Serdang, Malaysia. Participants will be equally randomized into three groups. Participants in the Control Group (n = 35) would receive no intervention and undergo usual follow-up. In comparison, those participants in the Intervention Groups (n = 70) would receive nutrition education to modify sugars consumption. They will also be given either refined white sugar (n = 35), or Minimally Refined Brown Sugar (n = 35) for daily consumption throughout a six-month study period. Measurements include socio-demographic status, medical characteristics, nutritional status, lifestyle practices, Health Belief Model constructs, and knowledge of healthy diet will be measured at baseline, first- (V1), third- (V3) and sixth-month (V6) intervals. Conclusion: Participants of both Intervention Group aiming for sugar intake modification, would have lower sugar consumption and better CMR-related outcomes than the Control Group. Since Minimally Refined Brown Sugar contains fair amount of antioxidants, participants of Intervention Group (Minimally Refined Brown Sugar) will have better CMR-related outcomes than participants of Intervention Group (white sugar) at the end of the study.